Association between left ventricular diastolic dysfunction and severity of chronic obstructive pulmonary disease - Caram, Laura Miranda de Oliveira; Ferrari, Renata; Naves, Cristiane Roberta; Tanni, Suzana Erico; Coelho, Liana Sousa; Zanati, Silméia Garcia; Minicucci, Marcos Ferreira [UNESP]; Godoy, Irma de [UNESP] (Universidade de São Paulo (USP), Faculdade de Medicina, 2013)
OBJECTIVES: ,,,,,The prevalence of electrocardiographic and echocardiographic abnormalities in chronic obstructive pulmonary disease according to disease severity has not yet been established. The aim of this study was to assess the prevalence of electrocardiographic and echocardiographic abnormalities in chronic obstructive pulmonary disease patients according to disease severity. ,,,, ,,,, ,,,,,METHODS: ,,,,,The study included 25 mild/moderate chronic obstructive pulmonary disease patients and 25 severe/very severe chronic obstructive pulmonary disease patients. All participants underwent clinical evaluation, spirometry and electrocardiography/echocardiography. ,,,, ,,,, ,,,,,RESULTS: ,,,,,Electrocardiography and echocardiography showed Q-wave alterations and segmental contractility in five (10%) patients. The most frequent echocardiographic finding was mild left diastolic dysfunction (88%), independent of chronic obstructive pulmonary disease stage. The proportion of right ventricular overload (p<0.05) and blockage of the anterosuperior division of the left bundle branch were higher in patients with greater obstruction. In an echocardiographic analysis, mild/moderate chronic obstructive pulmonary disease patients showed more abnormalities in segmental contractility (p<0.05), whereas severe/very severe chronic obstructive pulmonary disease patients showed a higher prevalence of right ventricular overload (p<0.05), increased right cardiac chamber (p<0.05) and higher values of E-wave deceleration time (p<0.05). Age, sex, systemic arterial hypertension, C-reactive protein and disease were included as independent variables in a multiple linear regression; only disease severity was predictive of the E-wave deceleration time [r2 = 0.26, p = 0.01]. ,,,, ,,,, ,,,,,CONCLUSION: ,,,,,Chronic obstructive pulmonary disease patients have a high prevalence of left ventricular diastolic dysfunction, which is associated with disease severity. Because of this association, it is important to exclude decompensated heart failure during chronic obstructive pulmonary disease exacerbation.
Keywords: Chronic Obstructive Pulmonary Disease; Electrocardiography; Echocardiography; GOLD; Spirometry